Ataxic Symptoms in Huntington’s Disease Transgenic Mouse Model Are Alleviated by Chlorzoxazone - Egorova, Polina A.; Gavrilova, Aleksandra V.; Bezprozvanny, Ilya B. (Frontiers in Neuroscience, 2020)
Huntington’s disease (HD) is a hereditary neurodegenerative disease caused by a polyglutamine expansion in the huntingtin protein, Striatum atrophy in HD leads to a progressive disturbance of psychiatric, motor, and cognitive function. Recent studies of HD patients revealed that the degeneration of cerebellum is also observed independently from the striatal atrophy during early HD stage and may contribute to the motor impairment and ataxia observed in HD. Cerebellar Purkinje cells (PCs) are responsible for the proper cerebellar pathways functioning and motor control. Recent studies on mouse models of HD have shown that the abnormality of the biochemical functions of PCs are observed in HD, suggesting the contribution of PC dysfunction and death to the impaired movement coordination observed in HD. To investigate ataxic symptoms in HD we performed a series of experiments with the yeast artificial chromosome transgenic mouse model of HD (YAC128). Using extracellular single-unit recording method we found that the portion of the cerebellar PCs with bursting and irregular patterns of spontaneous activity drastically rises in aged YAC128 HD mice when compared with wild type littermates. Previous studies demonstrated that SK channels are responsible for the cerebellar PC pacemaker activity and that positive modulation of SK channel activity exerted beneficial effects in different ataxic mouse models. Here we studied effects of the SK channels modulator chlorzoxazone (CHZ) on the motor behavior of YAC128 HD mice and also on the electrophysiological activity and neuroanatomy of the cerebellar PCs from these mice. We determined that the long-term intraperitoneal injections of CHZ alleviated the progressive impairment in the firing pattern of YAC128 PCs. We also demonstrated that treatment with CHZ rescued age-dependent motor incoordination and improved the cerebellar morphology in YAC128 mice. We propose that abnormal changes in the PC firing patterns might be a one of the possible causes of ataxic symptoms in HD and in other polyglutamine disorders and that the pharmacological activation of SK channels may serve as a potential way to improve the activity of cerebellar PCs and relieve the ataxic phenotype in HD patients.